On Pentakis(pentafluoroethyl)stannate, [Sn(C2F5)5]−, and the Gas‐Free Generation of Pentafluoroethyllithium, LiC2F5. Issue 8 (11th December 2017) - Wiesemann, Markus; Klösener, Johannes; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: Pentafluoroethyllithium, LiC2 F5, has been established as an efficient and versatile reagent for the transfer of the pentafluoroethyl unit to a number of electrophiles. Here, the stability of this species up to −40 °C is of advantage, particularly in comparison to its smaller congener LiCF3 . The usual production of LiC2 F5, however, from gaseous HC2 F5 or IC2 F5 and strong bases requires specially designed apparatuses, which severely impeded its value as a laboratory reagent. In this contribution we communicate an alternative gas‐free and highly efficient protocol for the synthesis of LiC2 F5 from the already commercialized stannate salt [PPh4 ][Sn(C2 F5 )5 ]. The [Sn(C2 F5 )5 ] − anion represents not only the first example of a structurally characterized hypervalent pentaalkylstannate but also serves as a precursor for the synthesis of the homoleptic tetrakis(pentafluoroethyl)stannane, Sn(C2 F5 )4 . The reaction of the latter with n‐ butyllithium provides an insight into the mechanism of LiC2 F5 generation. Abstract : Gas‐free pentafluoroethylation : Perfluoroalkylation reactions are often characterized by the tedious handling of gases, which lead to the development of numerous easy‐to‐handle perfluoroalkylation reagents. In the course of this the hypervalent [PPh4 ][Sn(C2 F5 )5 ] represents an easily accessible, storable and solid precursor for the generation of the highly reactive LiC2 F5 . Its reactivity and the separation of tin‐containing by‐products were shown in several pentafluoroethylation reactions.